Effect of Intranodally Administered Dendritic Cell-Based HIV Vaccine in Combination With Pegylated Interferon α-2a on Viral Control Following ART Discontinuation: A Phase 2A Randomized Clinical Trial - Leal, Lorna; Couto, Elvira; Sánchez-Palomino, Sonsoles; Climent, Núria; Fernández, Irene; Miralles, Laia; Romero, Yolanda; González, Tania; Maleno, Maria José; Paño, Blanca; Pich, Judit; Nicolau, Carlos; et al. (Frontiers in Immunology, 2021)
Introduction: Functional cure has been proposed as an alternative to life-long antiretroviral therapy and therapeutic vaccines represent one of the most promising approaches. Materials and Methods: We conducted a double-blind randomized placebo-controlled clinical trial, to evaluate the safety, immunogenicity and effect on viral dynamics of a therapeutic vaccine produced with monocyte-derived dendritic cells (MD-DC) loaded with a high dose of heat-inactivated autologous (HIA) HIV-1 in combination with pegylated Interferon α 2a (IFNα-2a) in HIV-1 chronic infected patients. Results: Twenty-nine male individuals on successful ART and with CD4+ ≥450 cells/mm3 were randomized 1:1:1:1 to receive 3 ultrasound guided inguinal intranodal immunizations, 1 every 2 weeks: 1) vaccine ~107MD-DC pulsed with HIA-HIV-1(1010 HIV RNA copies) (n=8); 2) vaccine plus 3 doses of 180mcg IFNα-2a at weeks 4-6 (n=6); 3) placebo=saline (n=7); and 4) placebo plus 3 doses of 180mcg IFNα-2a (n=8). Thereafter treatment was interrupted (ATI). Vaccines, IFNα-2a and the administration procedures were safe and well tolerated. All patients viral load rebounded during the 12 week ATI period. According to groups changes in viral set-point between pre-ART and during ATI were not significant. When comparing all groups there was a tendency in changes in viral set-point between the vaccine group vs vaccine + IFNα-2a group (>0.5log10 p=0.05). HIV-1 specific T-cell responses (IFN-ƴ Elispot) were higher at baseline in placebo than in vaccine group (2259±535 vs 900±200 SFC/106 PBMC, p=0.028). A significant difference in the change of specific T-cell responses was only observed at week 4 between vaccine and placebo groups (694±327 vs 1718±282 SFC/106 PBMC, p=0.04). No effect on T cell responses neither changes in viral reservoir were observed after INFα-2a administration. Discussion: Results from this study show that intranodally administered DC therapeutic vaccine in combination with IFNα-2a was safe and well-tolerated but had a minimal impact on viral dynamics in HIV-1 chronic infected patients. Clinical Trial Registration: www.ClinicalTrials.gov, identifier NCT02767193